Bridging the Digital Divide: The Imperative for Cyber Expertise Among Nepal’s Justices/Judges, Litigators, and Investigators - Bhattarai, Shree Krishna (KDCBAR Law Journal, 2025)
Digital evidence is becoming a common component of litigation across Nepal's legal spectrum, including civil disputes, criminal trials, constitutional writs, and administrative reviews. It is no longer limited to cybercrime cases and may be found in everything from WhatsApp conversations and emails to cloud records and GPS logs. Nevertheless, the revelation of this evidence has glaringly revealed a structural problem with Nepal's legal system. This article makes the case that Nepalese cyber jurisprudence has developed slowly and is now in a primitive state due to a lack of a strong legal framework, including a specific Digital/Electronic Evidence Act, Data Protection Act, Cybercrime Act, Social Media Act, and updated forensics legislation, as well as a serious lack of cyber literacy among judges, attorneys, investigators, and prosecutors. This article demonstrates how the absence of ISO-accredited Digital Forensics Labs, cyber-expert staff, and fundamental digital knowledge compromises fair trials, impedes justice, and compromises the integrity of the legal system by looking at the real-world difficulties encountered in routine cases. It concludes by making a compelling case for comprehensive capacity building among law enforcement officials, including judges, legal reform, the hiring of cyber-savvy judges, and the necessary integration of cyber competence at all levels of the legal profession in order to bridge the widening gap between technology and justice in Nepal.